Next Generation of Inorganic Composite Materials for Structural Strengthening: Development of Geopolymer Matrix - Papakonstantinou, Christos; Skyrianou, Ioanna; Koutas, Lampros (Technical Annals, 2024)
With the increasing need for strengthening seismically prone structures, the use of composite materials and specifically of textile-reinforced mortars (TRM) has increased. In an effort to develop the mechanical properties as well as reduce the carbon footprint of the materials used, new alternatives have been in the spotlight. The use of geopolymer mortars as a matrix in composite materials is a sustainable alternative to cement-based mortars. The current study experimentally investigates the compressive and flexural strength of metakaolin-based geopolymer mortars with the intent to optimize the mix design. Meanwhile, their properties are compared with commercially available cement-based mortars suitable for use as a matrix in TRMs. The investigated parameters for the mix design are the activator to precursor ratio and the gradation of the sand. Based on the results, the activator to precursor ratio is a significant parameter affecting the strength and workability of the mortars. On the contrary, the sand gradation seemed to affect mostly the workability rather than the strength. In comparison to the cement-based mortars studied, geopolymer mortars exhibited comparable and, in some cases, even higher compressive and flexural strength.